Lightweight filling material as well as preparation method and use method thereof
By preparing lightweight filling materials, the problem of separation difficulties in ultra-high water filling materials and crystallization water precipitation during coal preparation is solved, and efficient coal mine filling and transportation is achieved, which improves the purity and compressive strength of coal and reduces transportation. Cost and environmental impact.
Patent Information
- Application Number
- CN202411339938.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-25
- Publication Date
- 2024-12-17
- Estimated Expiration
- 2044-09-25
AI Technical Summary
The existing ultra-high water filling materials cannot be effectively separated during the coal preparation process, and the condensate contains a large amount of crystal water, which causes the coal belt machine to slip and the coal seam to collapse, affecting the coal use effect.
Composition A and composition B with a mass ratio of 1:1, comprising water, silicate cement clinker, fly ash and sodium percarbonate, and composition B comprises water, lime, gypsum and stone powder, by Grind and mix to prepare the slurry, and after transportation, mix at the designated location to form a lightweight filling material with a density of 300-900kg/m³, with a compressive strength of 0.23-16MPa to avoid precipitation of crystallization water.
It realizes effective washing and selection of lightweight filling materials, improves the purity of coal, increases the compressive strength range, reduces transportation costs, avoids coal machine failures, and has environmentally friendly and economical materials.
Abstract
Description
Technical Field
[0001] The invention relates to the field of filling, and in particular to a lightweight filling material and a preparation method and a use method thereof. Background Art
[0002] Lightweight filling materials are mainly used for filling the damaged area of small kilns in coal mines. The existing small kiln damaged area filling mainly uses ultra-high water filling materials, which have a simple construction process. However, when it is necessary to remove the mixed filling materials in the coal through coal selection after filling, since most coal preparation plants use heavy medium coal selection, this method requires that the density of the impurities (including filling materials) washed out is greater than that of coal in order to separate the coal and impurities. The density of ultra-high water crystal water filler is about 1.2t / m³, which is less than that of coal (such as anthracite), so the filling material cannot be washed out. As a result, due to the presence of the filling material, the final coal has more impurities, which affects the use effect of the coal.
[0003] At the same time, in the prior art, since the water-cement ratio of the ultra-high water filling material is relatively high, the condensate obtained after the filling material solidifies contains a large amount of crystalline water. After the condensate is cut by the coal machine, the water is easily precipitated, which can easily cause the coal machine's belt conveyor to slip or even the coal seam to burst. Summary of the invention
[0004] In order to solve the above technical problems, the present invention provides a lightweight filling material which is easy to wash and does not easily precipitate crystal water.
[0005] In order to achieve the technical effects of the present invention, the following technical solutions are adopted: A lightweight filling material, wherein the raw materials for preparing the lightweight filling material include a composition A and a composition B in a mass ratio of 1:1, wherein the composition A includes the following components in parts by mass: 60-75 parts of water, 70-75 parts of Portland cement clinker, 15-22 parts of fly ash, and 8-10 parts of sodium percarbonate; Composition B includes the following components by mass: 60-75 parts of water, 25-30 parts of lime, 47-50 parts of gypsum, 8-18 parts of stone powder, and 10-12 parts of foam stabilizer; The preparation method of the lightweight filling material comprises the following steps: (1) Grinding the silicate cement clinker in composition A to a specific surface area of more than 300 m2 / kg, then mixing it with fly ash and sodium percarbonate, and adding water to prepare slurry A; mixing the lime, gypsum, stone powder and foam stabilizer in composition B, and adding water to prepare slurry B; (2) After slurry A and slurry B are transported separately, slurry A and slurry B are mixed and stirred evenly to obtain a material slurry (i.e., a lightweight filling material); after the material slurry is filled to the position to be filled, it can be solidified and formed to obtain a filling body, and the density of the filling body is 300-900kg / m³ and the compressive strength is 0.23-16MPa.
[0006] As a further improvement, the step (2) is to mix the slurry A and the slurry B after transporting the slurry A and the slurry B for 50-2000 meters respectively.
[0007] As a further improvement, the content of clinker and gypsum in the silicate cement clinker is greater than 80%; the conveying flow rate in the step (2) is 10 cubic meters per hour, and the inner diameter of the pipeline for conveying slurry A and slurry B is 32 mm.
[0008] As a further improvement, the content of clinker and gypsum in the silicate cement clinker is greater than 80%, and the content of effective ingredients is high, which can well meet the requirements.
[0009] As a further improvement, the fly ash is primary fly ash.
[0010] As a further improvement, the effective components of the lime and gypsum are above 90%, and the residues of the lime and gypsum on a 0.08 mm sieve are both less than 10%. In this way, the reaction is more complete.
[0011] As a further improvement, the stone powder includes one or a combination of limestone powder, dolomite powder and quartz powder.
[0012] As a further improvement, in step (1), the silicate cement clinker in composition A is ground to a specific surface area of more than 300 m2 / kg, then mixed with fly ash and sodium percarbonate, and stirred with water for 3-5 minutes to obtain slurry A; the lime, gypsum, stone powder and foam stabilizer in composition B are mixed, and stirred with water for 3-5 minutes to obtain slurry B.
[0013] As a further improvement, in step (2), slurry A and slurry B are mixed and stirred for 1 minute to obtain a material slurry with a temperature of 16-25°C.
[0014] The present invention also provides a method for using the lightweight filling material described above, which is as follows: fill the material slurry into the position that needs to be filled, and after the material slurry is solidified and formed, a filling body is obtained; the position that needs to be filled is the position that needs to be filled in the underground tunnel; such as: an empty area or an empty tunnel underground.
[0015] In the present invention, heat is provided by the exothermic reaction of lime and water, so that the sodium percarbonate and water are prompted to react to generate oxygen bubbles, and the foam stabilizer is used to extend the existence time of the foam. The stone powder is used to increase the fluidity and workability of the composition B, slurry A and slurry B. At the same time, the stone powder can be used to adjust the strength of the filling body, thereby obtaining a filling body with a small density and a wide range of compressive strength.
[0016] By adding fly ash, the fluidity and workability of the composition A, slurry A and slurry B are increased. Various substances cooperate with each other to obtain a lightweight filling material with superior performance.
[0017] At the same time, in the prior art, the on-site construction environment is complex and the production equipment (such as grouting pump) is difficult to adjust. In order to ensure the smooth progress of production, the mass ratio of composition A and composition B will be adjusted to 1:1. In addition, since gypsum easily absorbs water, the slurry is easy to coagulate, and it is not easy to cause coagulation due to excessive addition of water, thus ensuring normal production.
[0018] The present invention has the following beneficial effects: 1. The beneficial effects of the preparation method of the present invention include: Since slurry A and slurry B are transported separately, during the transportation process, the temperature of slurry A is relatively low, and sodium percarbonate is not easy to react and produce bubbles. During the transportation process of slurry B, lime reacts with water and releases heat. When it reaches the designated location, due to the high temperature of slurry B, when slurry A and slurry B are mixed, the temperature of the mixture (material slurry) is relatively high, which prompts sodium percarbonate to react with water and release bubbles, thereby obtaining a lightweight filling material with superior performance. Compared with slurry A and slurry B mixed before transportation, it can greatly increase the transportation distance. For places with high space restrictions, such as underground coal mines, it is very difficult to transport solid materials due to limited space. By mixing solid materials with water and then sending them in through pipelines, compared with slurry A and slurry B condensed before transportation, a large amount of transportation resources can be saved, transportation costs can be reduced, and energy consumption can be reduced. At the same time, slurry A and slurry B are transported first and then mixed, which can also reduce the density of the filling body. When the compressive strength requirement is relatively high, it can greatly meet the needs of production and produce unexpected technical effects.
[0019] 2. The beneficial effects of the filler of the present invention include: 2.1. Lightness. The density of the filling body of the present invention is 300-900kg / m³, which is less than that of water. The filling body can be water-selected, and the light filling materials in the coal mine can be removed by water selection, thereby making it difficult for filling materials to be present in the coal mine, thereby improving the purity of the coal.
[0020] 2.2. Wide range of compressive strength. The compressive strength of the lightweight filling material prepared by the present invention can be adjusted between 0.23-16MPa, with a wide range of compressive strength. Compared with the narrow range of ultra-high water filling materials in the prior art (generally between 1.0-1.5MPa), the compressive strength range is increased and the application range is wider.
[0021] 2.3. Integrity: It can be cast on site according to different needs. Since the material is in liquid form when it enters the underground tunnel, the liquid will fill every space and can be tightly combined with the tunnel, thus it also has good water resistance.
[0022] 2.4. No crystal water will be precipitated: Due to the small water-cement ratio and small water consumption of the formula of the present invention, all the water participates in the hydration reaction, and there is no crystal water in the condensate, so no crystal water will be precipitated, which will not cause the coal machine belt conveyor to slip or even the coal seam to collapse. Compared with the existing ultra-high water filling materials, its condensate contains a large amount of crystal water, which produces unexpected technical effects.
[0023] 2.5. Environmental protection: The main raw materials used are siliceous materials and calcium materials existing in nature, which do not contain harmful substances, are pollution-free to the environment and have no fire hazards.
[0024] 2.6. Economical: The overall cost is low. DETAILED DESCRIPTION
[0025] Example 1
[0026] A lightweight filling material, the preparation raw materials of which include composition A and composition B in a mass ratio of 1:1, the composition A includes the following components in parts by mass: 60 parts of water, 70 parts of Portland cement clinker, 15 parts of fly ash, and 8 parts of sodium percarbonate; the composition B includes the following components in parts by mass: 60 parts of water, 25 parts of lime, 47 parts of gypsum, 11 parts of stone powder, and 10 parts of foam stabilizer.
[0027] Example 2
[0028] A lightweight filling material, wherein the raw materials for preparing the lightweight filling material include a composition A and a composition B in a mass ratio of 1:1, wherein the composition A includes the following components in parts by mass: 75 parts of water, 75 parts of Portland cement clinker, 22 parts of fly ash, and 10 parts of sodium percarbonate; Composition B includes the following components by mass: 75 parts of water, 30 parts of lime, 50 parts of gypsum, 18 parts of stone powder, and 12 parts of foam stabilizer.
[0029] Example 3
[0030] A lightweight filling material, wherein the raw materials for preparing the lightweight filling material are composition A and composition B in a mass ratio of 1:1, wherein the composition A comprises the following components in parts by mass: 75 parts of water, 75 parts of Portland cement clinker, 15 parts of fly ash, and 10 parts of sodium percarbonate; and the composition B comprises the following components in parts by mass: 75 parts of water, 30 parts of lime, 50 parts of gypsum, 8 parts of stone powder, and 12 parts of a foam stabilizer.
[0031] Example 4
[0032] A lightweight filling material, the preparation raw materials of which include composition A and composition B in a mass ratio of 1:1, the composition A includes the following components in parts by mass: 60 parts of water, 70 parts of Portland cement clinker, 22 parts of fly ash, and 8 parts of sodium percarbonate; the composition B includes the following components in parts by mass: 60 parts of water, 25 parts of lime, 47 parts of gypsum, 18 parts of stone powder, and 10 parts of foam stabilizer.
[0033] Comparative Example 1.1
[0034] The preparation raw materials are the same as those in Example 1, with the only difference being that stone powder is not added to composition B, the mass of other components in composition B is increased by 11 parts, and the mass ratio of other components added to composition B is water: lime: gypsum: foam stabilizer = 60:25:47:10.
[0035] Comparative Example 1.2
[0036] The raw materials for preparation are the same as those in Example 1, with the only difference being that no foam stabilizer is added to composition B, the mass of other components in composition B is increased by 10 parts, and the mass ratio of other components added to composition B is water: lime: gypsum: stone powder = 60:25:47:11.
[0037] Comparative Example 1.3
[0038] The raw materials for preparation are the same as those in Example 1, except that sodium percarbonate is not added to composition A, the mass of other components in composition A is increased by 8 parts, and the mass ratio of other components added in composition A is water: silicate cement clinker: fly ash = 60:70:15.
[0039] Comparative Example 1.4
[0040] The raw materials for preparation are the same as those in Example 1, except that lime is not added to composition B, the mass of other components in composition B is increased by 25 parts, and the mass ratio of other components added to composition B is water: gypsum: stone powder: foam stabilizer = 60: 47: 11: 10.
[0041] Comparative Example 1.5
[0042] The raw materials are the same as those in Example 1, and the difference between the preparation method and Example 1 is that in step (2) of the preparation method, there is no need to transport slurry A and slurry B separately for 1000 meters, and slurry A and slurry B are directly mixed and then transported for 1000 meters; the other preparation methods are the same as those in Example 1.
[0043] Comparative Example 1.6
[0044] The raw materials are the same as those in Example 1, and the difference between the preparation method and Example 1 is that in step (2) of the preparation method, slurry A and slurry B are transported for 50 meters respectively, and then slurry A and slurry B are mixed; the other preparation methods are the same as those in Example 1.
[0045] Comparative Example 3.1
[0046] The preparation raw materials are the same as those in Example 3, with the only difference being that stone powder is not added to composition B, the mass of other components in composition B is increased by 8 parts, and the mass ratio of other components added to composition B is water: lime: gypsum: foam stabilizer = 75:30:50:12.
[0047] Comparative Example 3.2
[0048] The preparation raw materials are the same as those in Example 3, with the only difference being that no foam stabilizer is added to composition B, the mass of other components in composition B is increased by 12 parts, and the mass ratio of other components added to composition B is water: lime: gypsum: stone powder = 75:30:50:8.
[0049] Comparative Example 3.3
[0050] The preparation raw materials are the same as those in Example 3, with the only difference being that sodium percarbonate is not added to composition A, the mass of other components in composition A is increased by 10 parts, and the mass ratio of other components added to composition A is water: silicate cement clinker: fly ash = 75:75:15.
[0051] Comparative Example 3.4
[0052] The raw materials for preparation are the same as those in Example 3, except that lime is not added to composition B, the mass of other components in composition B is increased by 30 parts, and the mass ratio of other components added to composition B is water: gypsum: stone powder: foam stabilizer = 75: 50: 8: 12.
[0053] Comparative Example 3.5
[0054] The raw materials are the same as those in Example 3, and the difference between the preparation method and Example 3 is that in step (2) of the preparation method, there is no need to transport slurry A and slurry B separately for 1000 meters, and slurry A and slurry B are directly mixed and then transported for 1000 meters; the other preparation methods are the same as those in Example 3.
[0055] Comparative Example 4.1
[0056] The preparation raw materials are the same as those in Example 4, with the only difference being that stone powder is not added to composition B, the mass of other components in composition B is increased by 18 parts, and the mass ratio of other components added to composition B is water: lime: gypsum: foam stabilizer = 60:25:47:10.
[0057] Comparative Example 4.2
[0058] The preparation raw materials are the same as those in Example 4, with the only difference being that no foam stabilizer is added to composition B, the mass of other components in composition B is increased by 10 parts, and the mass ratio of other components added to composition B is water: lime: gypsum: stone powder = 60:25:47:18.
[0059] Comparative Example 4.3
[0060] The preparation raw materials are the same as those in Example 4, with the only difference being that sodium percarbonate is not added to composition A, the mass of other components in composition A is increased by 8 parts, and the mass ratio of other components added to composition A is water: silicate cement clinker: fly ash = 60:70:22.
[0061] Comparative Example 4.4
[0062] The raw materials for preparation are the same as those in Example 4, except that lime is not added to composition B, the mass of other components in composition B is increased by 25 parts, and the mass ratio of other components added to composition B is water: gypsum: stone powder: foam stabilizer = 60: 47: 18: 10.
[0063] Comparative Example 4.5
[0064] The raw materials are the same as those in Example 4, and the difference between the preparation method and Example 4 is that in step (2) of the preparation method, there is no need to transport slurry A and slurry B separately for 1000 meters, and slurry A and slurry B are directly mixed and then transported for 1000 meters; the other preparation methods are the same as those in Example 1.
[0065] In each embodiment and comparative example, the raw materials used can be: in the silicate cement clinker, the content of clinker and gypsum is greater than 80%; the fly ash is first-class fly ash; the effective components of the lime and gypsum are both above 90%, and the residues of the lime and gypsum on a 0.08 mm fineness sieve are both less than 10%; the stone powder is limestone powder; the stone powder can also be one or a combination of limestone powder, dolomite powder, and quartz powder. The foam stabilizer model is AE-1450; it can be purchased from Nanjing Xinyi Synthetic Technology Co., Ltd.; brand: Xinyi Synthetic; model AE-1450; the trade name is also called powdered air entraining agent.
[0066] Preparation method
[0067] The preparation method of the filling material of embodiments 1, 2, 3, 4, 1.1-1.4, 3.1-3.4, 4.1-4.4 comprises the following steps: (1) The silicate cement clinker in composition A is ground to a specific surface area of more than 300 m2 / kg, then mixed with fly ash and sodium percarbonate, and stirred with water for 3-5 minutes to obtain slurry A; the lime, gypsum, stone powder and foam stabilizer in composition B are mixed, and stirred with water for 3-5 minutes to obtain slurry B.
[0068] (2) After slurry A and slurry B are transported for 1000 meters respectively, slurry A and slurry B are mixed and stirred evenly for 1 minute to obtain a material slurry with a temperature of 16-25°C; slurry A and slurry B can be transported by a double-liquid grouting pump (transport driving force) with a transport distance of 1000 meters. The rated transport flow rate of the double-liquid grouting pump is 10 cubic meters / hour, and the inner diameter of the pipeline (or pipe) for transporting slurry A and slurry B is 32 mm. The power of the double-liquid grouting pump is 22 kilowatts. Slurry A and slurry B can be transported at the same speed and arrive at the designated location at the same time.
[0069] The inner diameter of the pipe can also be selected as 25-51mm, but the inner diameter of 32mm is not easy to clog the pipe after a long period of use, nor will it cause the pipe to be clogged due to long-term use due to the pipe being too thick.
[0070] The method for using the filling material of embodiments 1, 2, 3, 1.1-1.6, 3.1-3.5, 4.1-4.5 comprises the following steps:
[0071] The method of use is: fill the material slurry to the position to be filled, and after the material slurry is solidified and formed, a filling body is obtained; the position to be filled is the position to be filled in the underground tunnel. The solidification time is 35-40 minutes.
[0072] For the convenience of testing, the material slurry is poured (filled) into a mold placed in an underground tunnel, solidified and formed into a material test block (also a filling body) for testing.
[0073] Effect test
[0074] Test method: 1. The method used for density test is: density test method in JGJ / T 70-2009 "Standard for Test Methods for Basic Properties of Building Mortar".
[0075] 2. The test method used for compressive strength test is: cube compressive strength test method in JGJ / T 70-2009 "Standard for Test Methods for Basic Properties of Building Mortar".
[0076] The test results are shown in Table 1.
[0077] Table 1
[0078] Example Density (kg / m³) Uniaxial compressive strength (MPa) Example 1 578 5.1 Example 2 425 1.6 Example 3 300 0.23 Example 4 900 16.0 Comparative Example 1.1 578 3.5 Comparative Example 1.2 868 7.9 Comparative Example 1.3 1736 19.1 Comparative Example 1.4 1446 12.9 Comparative Example 1.5 754 6.7 Comparative Example 1.6 578 5.1 Comparative Example 3.1 300 0.1 Comparative Example 3.2 500 1.0 Comparative Example 3.3 1666 18.0 Comparative Example 3.4 1400 12.0 Comparative Example 3.5 700 7.0 Comparative Example 4.1 900 8.0 Comparative Example 4.2 1500 23.0 Comparative Example 4.3 1777 25.0 Comparative Example 4.4 1480 13.4 Comparative Example 4.5 1110 17.1 Buy ultra high water filling materials on the market 1160 1.1
[0079] It can be seen from Table 1 that the lightweight filling material of the present invention has low density, wide compressive resistance range, can be well washed with water (it can remove the lightweight filling material in the coal through water washing, improve the purity of the coal, and meet the needs of use), and has a good application effect.
[0080] Composition A and composition B are used for transportation respectively, not only the prepared raw materials are of good quality, but also the transportation distance is long.
[0081] By mixing sodium percarbonate, foam stabilizer and stone powder, the density and compressive strength of the filling body can meet the requirements, producing unexpected technical effects.
[0082] The various components of the present invention cooperate with each other, and removing any one component may result in failure to meet the requirements of the use effect.
[0083] At the same time, the experiment found that when the raw materials, preparation methods and use methods of Examples 1-4 remain unchanged and the transportation distance is 2000 meters, the density and compressive strength of the filling body obtained are basically the same as when the transportation distance is 1000 meters.
[0084] In the present invention, the lime is quicklime.
[0085] The part in the present invention refers to part by mass, and may be kg, for example.
[0086] The above is only a preferred embodiment of the present invention, and it cannot be used to limit the scope of the present invention. That is, all simple equivalent changes and modifications made according to the contents recorded in the claims and the invention specification are still within the scope of the claims of the present invention. In addition, the abstract and title are only used to assist in searching patent documents, and are not used to limit the scope of the rights of the present invention.
Claims
1. A lightweight filling material, characterized in that: The raw materials for its preparation include composition A and composition B in a mass ratio of 1:1, and composition A includes the following components in parts by mass: 60-75 parts of water, 70-75 parts of Portland cement clinker, 15-22 parts of fly ash, 8-10 parts of sodium percarbonate; Composition B comprises the following components in parts by mass: 60-75 parts of water, 25-30 parts of lime, 47-50 parts of gypsum, 8-18 parts of stone powder, 10-12 parts of foam stabilizer; The preparation method of the lightweight filling material comprises the following steps: (1) Grinding the silicate cement clinker in composition A to a specific surface area of more than 300 m2 / kg, then mixing it with fly ash and sodium percarbonate, and adding water to prepare slurry A; mixing the lime, gypsum, stone powder and foam stabilizer in composition B, and adding water to prepare slurry B; (2) After slurry A and slurry B are transported separately, slurry A and slurry B are mixed and stirred evenly to obtain material slurry; After the material slurry is filled to the position to be filled, it can be solidified and formed to obtain a filling body. The density of the filling body is 300-900kg / m³ and the compressive strength is 0.23-16MPa.
2. A lightweight filling material as claimed in claim 1, characterized in that: The step (2) is to transport slurry A and slurry B for 50-2000 meters respectively and then mix slurry A and slurry B.
3. A lightweight filling material as claimed in claim 2, characterized in that: The content of clinker and gypsum in the silicate cement clinker is greater than 80%; the conveying flow rate in the step (2) is 10 cubic meters per hour, and the inner diameters of the pipelines for conveying slurry A and slurry B are both 32 mm.
4. A lightweight filling material as claimed in claim 1, characterized in that: The fly ash is primary fly ash.
5. A lightweight filling material as claimed in claim 1, characterized in that: The effective components of the lime and gypsum are both above 90%, and the residues of the lime and gypsum on a 0.08 mm sieve are both less than 10%.
6. A lightweight filling material as claimed in claim 1, characterized in that: The stone powder includes one or a combination of limestone powder, dolomite powder and quartz powder.
7. The method for preparing a lightweight filling material according to claim 1, characterized in that: In step (1), the silicate cement clinker in composition A is ground to a specific surface area of more than 300 m2 / kg, then mixed with fly ash and sodium percarbonate, and stirred with water for 3-5 minutes to obtain slurry A; the lime, gypsum, stone powder and foam stabilizer in composition B are mixed, and stirred with water for 3-5 minutes to obtain slurry B.
8. A method for preparing a lightweight filling material according to claim 7, characterized in that: In step (2), slurry A and slurry B are mixed and stirred for 1 minute to obtain a material slurry with a temperature of 16-25°C.
9. The method for preparing a lightweight filling material according to claim 1, characterized in that: The foam stabilizer model is AE-1450.
10. A method for using a lightweight filling material according to any one of claims 1 to 9, characterized in that: The method of using the device is as follows: fill the material slurry to the position that needs to be filled, and after the material slurry is solidified and formed, a filling body is obtained; the position that needs to be filled is the position that needs to be filled in the underground tunnel.
Citation Information
Patent Citations
Rapid-hardening inorganic filling support material for mine and using method of support material
CN104628414A
Light filling material for mines
CN107337412A
Foam filling material containing modified magnesium powder and preparation method of foaming filling material
CN109809830A
Cement composition and cavity filling material
JP2015134701A
Eco-friendly mortar composition for compaction grouting
KR101564382B1
